2018
DOI: 10.1038/s41550-018-0615-9
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a fundamental acceleration scale in galaxies

Abstract: Galaxies in the early universe appear to have grown too big too fast, assembling into massive, monolithic objects more rapidly than anticipated in the hierarchical ΛCDM structure formation paradigm. The available data are consistent with there being a population of massive galaxies that form early (z ≳ 10) and follow an approximately exponential star formation history with a short (≲ 1 Gyr) efolding timescale on the way to becoming massive (M * ≈ 10 11 M ⊙ ) galaxies by z = 0, consistent with the traditional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 117 publications
(228 reference statements)
0
23
0
Order By: Relevance
“…The existence of this acceleration scale has been confirmed by a wealth of observations on the scale of galaxies (e.g. [29,[91][92][93][94]). Indeed, the dynamics of disk and elliptical galaxies in the low-acceleration regime is described in the RG framework without requiring the existence of dark matter [72,74].…”
Section: The Gravitational Field Of a Spherical Source Immersed In A ...mentioning
confidence: 80%
See 1 more Smart Citation
“…The existence of this acceleration scale has been confirmed by a wealth of observations on the scale of galaxies (e.g. [29,[91][92][93][94]). Indeed, the dynamics of disk and elliptical galaxies in the low-acceleration regime is described in the RG framework without requiring the existence of dark matter [72,74].…”
Section: The Gravitational Field Of a Spherical Source Immersed In A ...mentioning
confidence: 80%
“…In addition, in the weak-field limit, Ξ sets an acceleration scale, (2Ξ) 1/2 ∼ 10 −10 m s −2 , below which RG deviates from Newtonian gravity and appears to describe the dynamics of disk and elliptical galaxies without the aid of dark matter [72,74]. This acceleration scale is indeed present in real systems [92,93] and is comparable to the acceleration a 0 introduced in MOND [36][37][38]. Therefore, CRG provides a connection between phenomena generally attributed to dark matter and dark energy separately.…”
Section: Discussionmentioning
confidence: 91%
“…where V f is the flat rotation velocity, M b is the total baryonic mass, and X is a factor of order unity that accounts for the cylindrical geometry of disks (McGaugh et al 2018). Fitting the data from Lelli et al (2019) in log-log space with LTS_LINEFIT (Cappellari et al 2013), we find that the best-fit slope is indistinguishable from 0.25 and the vertical intrinsic scatter is 0.02 dex along V f .…”
Section: Confirming the Constancy Of The Newtonian Gravitational Constantmentioning
confidence: 91%
“…They obtained a wide distribution of g † and concluded that a universal acceleration scale is ruled out. After substantial criticism about their methodology and interpretation of data (McGaugh et al 2018;Kroupa et al 2018;Cameron et al 2020), they presented a follow-up analysis in Marra et al (2020) in which they follow Li et al (2018) in adopting physically motivated Gaussian priors on distance, inclination, and stellar mass-to-light ratio. They persist in using a flat prior on g † , resulting in severe parameter degeneracies.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical value is given by There is presently a controversy about the validity of MOND. The research group of S. Mc Gaugh on November 13, 2018, published an article [64] in which the MOND hypothesis with a 0 = 1.15 × 10 −10 cm/s 2 has been confirmed contradicting the article by Rodrigues published on June 18, 2018, that arrived at the opposite result. In their reply to McGaugh's article [65][66][67], they upheld their conclusions questioning the statistical approach by S. McGaugh et al…”
Section: ν +mentioning
confidence: 96%